Effect of Dry Heat Puffing on Nutritional Composition, Fatty Acid, Amino Acid and Phenolic Profiles of Pseudocereals Grains - Paucar-Menacho, Luz María (2018)
This work was supported by the Ministry of Economy and Competitiveness (MINECO, Spain) and FEDER programme from the European Commission (grant number AGL2013–43247-R). E. P. acknowledges the MINECO and European Social Fund for her “Ramón y Cajal” grant. L. P-M. acknowledges the Consejo Nacional de Ciencia y Tecnología (CONCYTEC, Perú) for fi nancial support.